Improving Students’ Ability in Writing Persuasive News Texts Using Think Talk Write (TTW) Model of Second Year Students at Junior High School Muhammadiyah II Pekanbaru - Ihsan, Muhammad Taufik (Journal of English and Arabic Language Teaching, 2024)
The aims of this research to improve students’ ability in writing persuasive news texts using Think Talk Write (TTW) learning model with the type of Classroom Action Research (PTK) which is carried out in two stages, namely cycle I and cycle II with targets Minimum Completion Criteria (KKM), that is 75. The results of the analysis in this study show an increase from cycle I and cycle II. In cycle I, the number of scores obtained from class VIII A1 was 1,264 with an average score obtained of 63.2, which was in the poor category, while the number of scores obtained from class VIII A2 was 1,313 and if the average score was obtained at 65.65 which is in the poor category. In cycle II, the total scores obtained from class VIII A1 were 1,608 with an average score obtained of 80.4 in the good category, while the total scores obtained from class VIII A2 were 1,812 and if the average score obtained was 90.6 is in the very good category.